The imperial capital of Mâli (14th century) - François-Xavier Fauvelle (Medievalista)
Despite its international fame during the Middle Ages, our knowledge of the empire of Mâli remains patchy. Perhaps the most significant lacuna is that its capital has not yet been reliably identified. This paper offers a new hypothesis about the location of the imperial capital of Mâli in the 14th century. It is based on the observation that the rulers of Mâli, like those of other medieval African polities, strengthened their power by controlling the interface between opposite merchant networks. In doing so, they tended to establish their political legitimacy through the use of titles and displays of political and religious power befitting their different clients and subjects. Taking this economic, religious and political duality into consideration allows us to posit that the capital of Mâli lay outside the royal domain. Though it has not yet been probed by archaeology, the city’s hypothetical location proposed in this arricle corresponds to available Arabic descriptions.